From marine pollutant characterization to regional practice: implications of ITLOS Advisory Opinion No. 31 for the maritime sectors and Hainan FTP’s governance adaptation - Wang, Tingting; Sun, Yue (Frontiers in Marine Science, 2025)
The International Tribunal for the Law of the Sea (ITLOS) issued Advisory Opinion No.31 regarding the characterization of GHGs and obligations of the State Parties to UNCLOS. This study combines legal and policy research methods to forecast its implications on the maritime sectors and provide response suggestions. The legal analysis part employs a doctrinal legal analysis to examine obligations outlined in the ITLOS Opinion and relevant international instruments, and a socio-legal analysis to examine the impacts of the ITLOS Opinion. The policy research part adopts a qualitative approach to gather and review policy documents related to China’s involvement in “Green Shipping Corridor” initiatives and port policies, and conducts a case study analysis to select Hainan Province as a representative example for development suggestions. Our study showed that the ITLOS opinion No. 31 plays a catalytic role in global shipping decarbonization and may trigger a series of ripple effects on the global maritime sector. As China’s only Free Trade Port (FTP)and the special province connecting East Asian and Southeast Asian countries, Hainan Province is suggested to monitor advancements in global energy technology and track orders for “green vessels” to forecast future demand for green shipping fuels accurately; establish “green shipping corridors” through regional cooperation mechanisms among the South China Sea region; and apply preferential national policies for pilot programs in green shipping energy supply by use of the FTP status.